The three Graces of Val-Kill : Eleanor Roosevelt, Marion Dickerman, and Nancy Cook in the place they made their own - Wilson, Emily Herring (The University of North Carolina Press, 2017)
This title examines the most formative period in Eleanor Roosevelt's life, from 1922 to 1936, when she cultivated an intimate friendship with Marion Dickerman and Nancy Cook, who helped her build a cottage on the Val-Kill Creek in Hyde Park on the Roosevelt family land. Wilson takes care to show all the nuances and complexities of the women's relationship, which blended the political with the personal.